BASAMAKLI ÖĞRETİM MODELİNİN ÖĞRENCİLERİN YARATICI YAZMA BAŞARILARINA ETKİSİ - BAYDOĞAN, ÜMMÜHAN GÜZEL (Fırat Üniveristesi, 2024)
Yazmak; duygularımızın bir yansıması, yaratıcılığımızın kâğıt üzerindeki karşılığı, zihinsel bir gelişim aracı, bilinçli bir eylem ve kimi zaman da bir terapi unsurudur. Aynı zamanda öz güven, öz bilinç, yaratıcılık, özerklik gibi yetileri geliştirici niteliktedir. Buna rağmen motivasyon yetersizliği ve olumsuz tutum nedeniyle uygulama süreçlerinde öğrenciler tarafından yeterince tercih edilmemektedir. Zamanla geliştirilebilen bir beceri olmasına bağlı olarak pek çok öğrenci bu hususta kendi potansiyelinin farkına varamamaktadır. Çağımızın güncel öğretim tekniklerinden biri olan basamaklı öğretim programı ile öğrencilerin çalışmalardaki motivasyonları desteklenerek sorumluluk sahibi olmaları, kolaydan zora öğrenmeler gerçekleştirmeleri, üreticiliklerinin farkına varmaları, öz güven ve öz denetim bilinci edinmeleri amaçlanmaktadır. Bu nedenle araştırmada basamaklı öğretim programı ve yaratıcı yazmayı bir araya getirerek basamaklı öğretim programına dayalı olarak uygulanan yaratıcı yazma çalışmalarının öğrencilerin yaratıcı yazma başarılarına etkisini belirlemeyi amaçladık. Bu doğrultuda araştırma; karma yöntemle gerçekleştirilmiş ve açıklayıcı sıralı desen kullanılmıştır. Nitel ve nicel verilerin farklı zamanlarda toplandığı bu desende nicel boyut verilerini toplamak için Kasap (2019) tarafından geliştirilen Yaratıcı Yazma Ürünlerini Değerlendirme Ölçeği'nden (YARYÜDÖ) yararlanılmıştır. Araştırmanın nicel boyutunda Millî Eğitim Bakanlığından ve Antalya İl Millî Eğitim Müdürlüğünden gerekli izinler alınarak 2022-2023 eğitim-öğretim yılı içerisinde Antalya ilinde yer alan bir devlet okulunun 6. sınıf düzeyindeki 2 şubesinde 8+2 haftalık süre boyunca çalışmalar yürütülmüştür. Nicel veriler, yarı deneysel desende toplanmış; ön test-son test kontrol gruplu desenin uygulanması sırasında yansız atama yöntemi doğrultusunda deney ve kontrol grubu olarak iki çalışma grubu belirlenmiştir. Çalışmanın evren ve örnekleminin belirlenmesinde seçkisiz olmayan örnekleme yöntemlerinden amaçlı örnekleme yollarına başvurulmuştur. Araştırmanın evrenini uygun örnekleme yoluyla belirlenen bir devlet okulunun 6. sınıf öğrencileri, örneklemini ise tipik durum örnekleme ile evrenin içinden belirlenen 43 öğrenci (23 deney grubu, 20 kontrol grubu) oluşturmaktadır. Çalışma gruplarının belirlenmesi sürecinde ise ölçüt örneklemeye başvurulmuş ve çalışmanın iç tutarlılığını sağlamak üzere araştırmada deney grubu ve kontrol grubu öğrencilerinin 5. sınıf sene sonu Türkçe dersi puan ortalamaları dikkate alınmıştır. Yapılan Mann-Whitney U testi sonucunda deney grubu öğrencilerinin sene sonu puanlarıyla kontrol grubu öğrencilerinin sene sonu puanları arasında istatistiksel olarak anlamlı bir fark bulunmamıştır. Birbirine denk olduğu söylenebilen bu iki gruptan ise rastgele biri deney, diğeri kontrol grubunu oluşturmuştur. Araştırmanın nitel boyutunda nitel araştırma desenlerinden olan olgubilimsel (fenomenolojik) desen kullanılmıştır. Nicel verilerin analizinden elde edilen bulgular doğrultusunda nitel verileri toplamak için yarı yapılandırılmış görüşme kılavuzu tasarlanmıştır. Öğretmen görüşü doğrultusunda gönüllülük esası ile belirlenen 13 öğrenci nitel yöntemin çalışma grubunu oluşturmuştur. Öğrencilerle 9 sorudan oluşan, uygulama öğretmeniyle de 6 sorudan oluşan yarı yapılandırılmış görüşmelerle nitel veriler toplanmıştır. Ayrıca uygulamalar esnasında yapılandırılmamış gözleme de başvurulmuş ve tüm süreçten elde edilen bulgular nitel veri olarak kullanılmıştır. Araştırmanın nicel verilerinin analizinde YARYÜDÖ ile öğrencilerin yaptığı yaratıcı yazma çalışmaları değerlendirilmiş ve SPSS programı kullanılarak analiz edilmiştir. Verilerin normalliği Shapiro-Wilk normallik testiyle belirlenmiştir. Dağılımın normal dağılım göstermesi durumunda parametrik testlere, normal dağılım göstermemesi durumunda ise parametrik olmayan testlere başvurulmuştur. Gruplar arasındaki anlamlı farklılığın belirlenmesi sürecinde Kovaryans Analizi (ANCOVA) uygulanmıştır. Anlamlı farklılıkların belirlendiği testlerde de etki büyüklüğünün tespiti için Cohen'in formulünden yararlanlmıştır. Araştırmanın nitel boyutunda öğrencilerin ve uygulama öğretmeninin basamaklı öğretim programının yaratıcı yazma becerisine etkisine ilişkin görüşleri belirlenerek nicel bulguların desteklenmesi amaçlanmıştır. Yarı yapılandırılmış görüşme tekniği ve yapılandırılmamış gözlemden yararlanılarak veriler toplanmıştır. Bu veriler MAXQDA programına aktarılarak içerik ve betimsel analiz ile analizler gerçekleştirilmiş, kodlamalar yapılmıştır. Gözlemden elde edilen veriler de analizler sonucunda ulaşılan bulgularla değerlendirilmiştir. Ayrıca nitel araştırmanın güvenirliği için üçgenleme tekniğiyle çoklu yönteme başvurulmuştur. Nicel ve nitel aşamalardaki veri kümelerinin toplanarak analizinden sonra, araştırma sürecinin en son basamağında birleştirme aşaması gerçekleştirilmiştir. Bu araştırmanın sonuçları kapsamında yaratıcı yazma ürünlerinin değerlendirilmesinde ön test ve son testte deney grubu lehine yüksek; kalıcılık testinde ise orta etki değerine sahip anlamlı farklılıklar elde edilmiştir. Deney grubu öğrencilerinin başarı puan ortalamalarının her testte yükseldiği, kontrol grubu öğrencilerinin başarı puanlarının ise gerilemiş olduğu belirlenmiştir. Basamaklı Öğretim Programı (BÖP) uygulanan Deney Grubu (DG) öğrencilerinin cinsiyet değişkenine göre yaratıcı yazmaya yönelik ön test puanlarının erkek öğrencilerin lehine ve yüksek etki değerine sahip olarak anlamlı bir şekilde farklılaştığı da bir diğer nicel bulgudur. DG öğrencilerinin son test ve kalıcılık testi puanlarında ise cinsiyet değişkenine göre anlamlı bir fark bulunamamıştır. Bununla birlikte aritmetik ortalamalara baktığımızda son test verilerine kıyasla her iki cinsiyette de kalıcılık testi puanlarının arttığı görülmüştür. Nicel verilerden ulaştığımız sonuçlar DG öğrencileriyle ve uygulama öğretmeniyle yapılan görüşmelerden elde edilen nitel verilerle de desteklenmiştir. Nitel analizlerde katılımcıların yazma uygulamaları sonucunda daha yaratıcı, daha özgür, öz denetim sahibi, özerk, mevcut öğrenmelerini farklı derslere aktarabilen, öz güveni yüksek, başarma zevkine varmış, ders başarısı artmış ve üretken öğrenciler oldukları sonucuna ulaşılmıştır. Gözlem verilerinin de bu sonuçları desteklediği belirlenmiştir. Elde edilen sonuçlardan hareketle alan araştırmacılarına, ders öğretmenlerine, kurumlara ve ailelere yönelik önerilerde bulunulmuştur.

To write; It is an entity of our emotions, the counterpart of our creativity on paper, a mental development tool, a conscious action and sometimes an element of therapy. It also improves skills such as self-confidence, creativity and autonomy. Despite this, it is not preferred enough by students during the implementing process due to lack of motivation and negative attitudes. Since it is a skill that can be developed over time, many students cannot realize their potential in this regard. With the layered curriculum, which is one of the current teaching techniques of our age, it is aimed to support students' motivation in studies, to make them responsible, to learn from easy to difficult, to realize their productivity, and to gain self-confidence and self-control awareness. For this reason, in the research, we aimed to bring together the layered curriculum and creative writing and determine the effect of creative writing exercises based on the layered curriculum on students' creative writing success. Research in this direction; It was carried out by mixed method and an explanatory sequential design was used. In this design where qualitative and quantitative data were collected at different times, the Creative Writing Products Evaluation Scale developed by Kasap (2019) was used to collect the quantitative dimension data. In the quantitative aspect of the research, necessary permissions were obtained from the Ministry of National Education and Antalya Provincial Directorate of National Education. In the 2022-2023 academic year, studies were carried out for a period of 8 + 2 weeks in two 6th grade branches of a public school in Antalya. Quantitative data were collected in a quasi-experimental design; during the practice of the pretest-posttest control group design, two study groups were determined as the experimental and control groups by the unbiased assignment method. Purposive sampling, one of the non-random sampling methods, was used to determine the population and sample of the study. The population of the research consists of 6th grade students of a public school determined by convenience sampling, and the sample consists of 43 students (23 experimental group, 20 control group) determined from the population by typical case sampling. In the process of determining the study groups, criterion sampling was used and in order to ensure the internal consistency of the study, the 5th grade end-of-year Turkish course average scores of the experimental group and control group students were taken into consideration. As a result of the Mann-Whitney U test, no statistically significant difference was found between the end-of-year scores of the experimental group students and the end-of-year scores of the control group students. Of these two groups, which can be said to be equivalent to each other, one randomly formed the experimental group and the other the control group. In the qualitative dimension of the research, phenomenological design, which is one of the qualitative research designs, was used. A semi-structured interview guide was designed to collect qualitative data in line with the findings obtained from the analysis of quantitative data. 13 students, determined on a voluntary basis in line with the teacher's opinion, formed the study group of the qualitative method. Qualitative data were collected through semi-structured interviews consisting of 9 questions with the students and 6 questions with the mentor teacher. In addition, unstructured observation was also used during the practices and the findings obtained from the whole process were used as qualitative data. In the analysis of the quantitative data of the research, the creative writing works of the students were evaluated with YARYÜDÖ and analyzed using the SPSS program. If the distribution showed a normal distribution, parametric tests were used, and if it did not show a normal distribution, non-parametric tests were used. Analysis of Covariance (ANCOVA) was applied in the process of determining significant differences between groups. In tests where significant differences were determined, Cohen's formula was used to determine the effect size. In the qualitative dimension of the research, it was aimed to support the quantitative findings by determining the opinions of the students and the mentor teacher regarding the effect of the layered curriculum on creative writing success. Data was collected using semi-structured interview technique and unstructured observation. These data were transferred to the MAXQDA program, content and descriptive analysis were performed, and coding was done. The data obtained from the observation was also evaluated with the findings obtained as a result of the analysis. In addition, for the reliability of the qualitative research, multiple methods were used with the triangulation technique. After collecting and analyzing the data sets in the quantitative and qualitative stages, the combining phase was carried out in the last step of the research process. Based on the results obtained, suggestions were made for field researchers, course teachers, institutions and families. As a result of this research, significant differences with high impact values were obtained in favor of the experimental group in the pre-test and post-test in the evaluation of creative writing products. In the permanence test of the experimental group, a significant difference with a medium effect value was reached. It was determined that the average success scores of the experimental group students increased gradually in each test, while the success scores of the control group students decreased gradually. Another quantitative finding is that the pre-test scores for creative writing of the experimental group students, to whom the layered curriculum was applied, differed significantly according to the gender variable, in favor of the male students and with a high impact value. No significant difference was found in the posttest and retention test scores of the experimental group students according to the gender variable. However, when we look at the arithmetic averages, it was seen that the retention test scores increased in both genders compared to the post-test data. The results we reached from the quantitative data were also supported by the qualitative data obtained from the interviews with the experimental group students and the application teacher. In the qualitative analysis, it was concluded that as a result of the writing practices, the participants became more creative, freer, self-controlled, autonomous, able to transfer their current learning to different courses, had high self-confidence, enjoyed success, increased course success, and were productive students. It was determined that observation data also supported these results.
The effect of the layered curriculum on students' creative writing achievements
Keywords: Eğitim ve Öğretim